Fetal Ascites in a Perosomus Elumbis Fetal Monster in a Cross Bred Cow - Vadera, Vishnu; Sahu, Uttam Kumar; Warghat, Chinmay; Muthuswamy, Aadhithya; Kumar, Brijesh (Animal Reproduction Update, 2025)
A 7-year-old crossbred cow was brought to the Referral Veterinary Polyclinic of the  Indian Veterinary Research Institute, India, with a history of continuous straining  for the past 12 h. Per vaginal examination, the presence of a foetus with severe ascites  was revealed. Gross examination confirmed the dead foetus, with the abdominal and  thoracic cavities filled with fluid. The condition was successfully managed through  obstetrical manipulation.
Keywords: Crossbreed cow; Dystocia; Foetal ascites; Persomus elumbis